AUTOCHTHONOUS BIOFACIES IN THE PLIOCENE LORETO BASIN, BAJA CALIFORNIA SUR, MEXICO (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1998)
The present paper examines the molluscan and/or echinoid assemblages recovered from two lithostratigraphic units (Piedras Rodadas Sandstone and Arroyo de Arce Norte Sandstone) outcropping in the Pliocene Loreto Basin, Baja California Sur, Mexico. Ten biofacies have been identified, i.e. Trachycardium procerum-Trachycardium senticosum Biofacies, Chione compta-Transennella modesta Biofacies, Laevicardium elenense-Chione kelletii Biofacies, Xenophora sp. 1-Strombus subgracilior Biofacies, Crassostrea californica osunai Biofacies, Myrakeena angelica Biofacies, Vermetid-Nodipecten Biofacies, Argopecten abietis abietis Biofacies, Aequipecten dallasi Biofacies and Encope Biofacies. The first four biofacies have been defined on the basis of statistical analyses (cluster analysis, MDS). The other six, which are monospecific or definitely low-diversity, were already identified during field work. The deduced paleoecological bearing of biofacies, largely relying upon the comparison to their closest modern counterparts, provides the basis for the paleoenvironmental reconstruction. The latter also considers sedimentological evidence and is framed within the tectonic and sedimentary context recently proposed by American workers. Biofacies point toward environments differing in terms of substrate texture, presence/absence of vegetal cover, energy level, variously distributed within the low tide mark-40 m bathymetric range.